Pollutant transport and residence time of a shallow and narrow coastal lagoon estimated using a numerical model - Mohd Fadzil Akhir (Tanjung Malim, 2021)
Pollutant transport and residence time of a shallow and narrow coastal lagoon estimated using a numerical model by Mohd Fadzil Akhir